Efektivitas Penyelesaian Sengketa Internasional oleh ICJ: Studi Kasus Nigeria-Kamerun - Rahmadhana, Radya Alluna (Media Hukum Indonesia (MHI), 2025)
The territorial dispute over Bakassi between Nigeria and Cameroon is a significant example of international dispute resolution through the International Court of Justice (ICJ). This article examines the effectiveness of the ICJ in resolving the maritime dispute between the two countries, highlighting the legal process from the case submission in 1994 to the implementation of the ruling in 2002, which resulted in the transfer of the Bakassi Peninsula to Cameroon. The study analyzes the stages of legal resolution, challenges during implementation, and the socio-political impact of the ICJ’s decision on both nations. The findings indicate that the ICJ mechanism is effective in providing a legally binding peaceful solution, although successful implementation heavily depends on the political commitment and continued diplomacy of the involved states. This case study underscores the crucial role of the International Court of Justice in upholding international law and serves as a reference for resolving similar disputes in the future